Ensino de Geografia e Literatura: os transportes em Baião a partir de Eça e Redol - Pacheco, Elsa (2017)
This work reports a didactic experience of Geography in the scope of higher education. It is part of the intersection of two literary works - one was wrote by Eça de Queirós, in 1901, and another was wrote by Alves Redol, in 1946 -, which are related to the same territory (Baião), with the aim to test methodologies of teaching Geography from Literature sources. This didactic experience materialized in the reading of the works of Eça and Redol, in the research of historical and geographic documentation of support to the analysis of the transport dynamics and in fieldwork. In the field, through the identification, in loco, of the landscapes alluding to the mentioned transport in those literary works As a result, besides to being an incentive to the reading of great portuguese authors, the use of literary information that describes places in different periods constitutes, by comparison with a third moment - the present, subject of great importance for understanding the dynamics of alteration territories alteration, even because it introduces more realism and interest both in reading those novels, either in understanding the evolution of modes of transport and landscapes.